-41=-h+6h+13h

Simple and best practice solution for -41=-h+6h+13h equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -41=-h+6h+13h equation:


Simplifying
-41 = -1h + 6h + 13h

Combine like terms: -1h + 6h = 5h
-41 = 5h + 13h

Combine like terms: 5h + 13h = 18h
-41 = 18h

Solving
-41 = 18h

Solving for variable 'h'.

Move all terms containing h to the left, all other terms to the right.

Add '-18h' to each side of the equation.
-41 + -18h = 18h + -18h

Combine like terms: 18h + -18h = 0
-41 + -18h = 0

Add '41' to each side of the equation.
-41 + 41 + -18h = 0 + 41

Combine like terms: -41 + 41 = 0
0 + -18h = 0 + 41
-18h = 0 + 41

Combine like terms: 0 + 41 = 41
-18h = 41

Divide each side by '-18'.
h = -2.277777778

Simplifying
h = -2.277777778

See similar equations:

| y=sqrtx-7 | | 12s+72=8s+4(3s+18) | | x+(x+2)+(x+4)+(x+6)+(x+8)=435 | | 9x^2-3x-11=0 | | x+(x+2)+(x+4)+(x+6)+(x+8)=140 | | Y=20000+.3 | | 24-a=-15 | | Y=2000+.3 | | X^3-3xy+2y^2=0 | | 5y+2=-8y-11 | | 2(3x-4)+7=-4(3x-2) | | 787.5+4.9x=875+3.5x | | (u-8)*10=18 | | 1000x=281421906 | | b+2b+3b-22=4(b+6) | | -26=13t | | -16=6x-1 | | -6v+4(v+3)=-4 | | 400x=1000 | | 7a^2-42=35a | | 33=y+16 | | 12x^3+68x^2+84x= | | 5(n-3)=7+3m | | (6x-3-4)=(4x+14) | | 2x+32+x^2=80 | | 28*60=14x | | 125x-8x^4= | | 42=4n-7(n-9) | | 2x-22=-8 | | (6x-34)=(4x+14) | | x^3+4*x^2+6x+1=0 | | 2x+2x+(x+10)+50=40 |

Equations solver categories